2020
DOI: 10.3390/nu12082214
|View full text |Cite
|
Sign up to set email alerts
|

What Healthcare Professionals Think of “Nutrition & Diet” Apps: An International Survey

Abstract: Accurate dietary assessment is crucial for both the prevention and treatment of nutrition-related diseases. Since mobile-based dietary assessment solutions are promising, we sought to examine the acceptability of “Nutrition and Diet” (ND) apps by Healthcare Professionals (HCP), explore their preferences on apps’ features and identify predictors of acceptance. A 23 question survey was developed by an interdisciplinary team and pilot-tested. The survey was completed by 1001 HCP from 73 countries and 6 continents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 20 publications
2
47
0
1
Order By: Relevance
“…In line with our results, professionals suggested that funds, mHealth literacy, commercially developed apps, and lack of advocacy could also be potential barriers to recommend app use [35]. Moreover, similar to the midwives in our study, professionals indicated that an app should be easy to use (87%), self-explanatory (51%), and validated (69%) in order for them to recommend use of such an app [34]. In line with these findings, Verkasalo et al [36] summarised earlier research on the general use of apps and concluded that efficiency, simplicity, and pleasure are key predictors of the continuous use of apps by end-users.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In line with our results, professionals suggested that funds, mHealth literacy, commercially developed apps, and lack of advocacy could also be potential barriers to recommend app use [35]. Moreover, similar to the midwives in our study, professionals indicated that an app should be easy to use (87%), self-explanatory (51%), and validated (69%) in order for them to recommend use of such an app [34]. In line with these findings, Verkasalo et al [36] summarised earlier research on the general use of apps and concluded that efficiency, simplicity, and pleasure are key predictors of the continuous use of apps by end-users.…”
Section: Discussionsupporting
confidence: 86%
“…However, some midwives were reluctant and/or unfamiliar with the use of mHealth apps and indicated that information provision on this topic through the Dutch professional network KNOV was minimal. These findings add to recent findings of a 23-question survey by Vasiloglou et al [34] completed by 1001 professionals, mostly female medical doctors, with a mean age of 34 (SD 10) years from 73 countries all over the globe showing that 46% of the professionals recommended nutritional mHealth apps to their patients. Of the 54% of the professionals that did not recommend the use of these apps, 23% was not aware of their existence.…”
Section: Discussionsupporting
confidence: 80%
“…This makes sense, given that end users and health care professionals who benefit from such apps should have their needs considered throughout the entire development process with tools and techniques, such as extensive surveys and periodic trial tests to facilitate this process. Thus, research is essential to outline how and when these apps may most efficiently aid those needs [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, to achieve high-quality data, both nutrition and computer scientists also need to focus on the behavioral aspects of data acquisition. In an international survey conducted among health care professionals (n=1001) in 6 continents, they mentioned that to recommend a Nutrition and Diet app to their patients or clients, they would prefer an app that is easy to use (87.1%), validated (68.1%), supports automatic food recording (56.5%), and automatically outputs nutrient estimations (52.4%) [ 18 ]. However, accurate data for food quality assessments can only be based on the correct capture of meal images, which is of vital importance if smartphones are to be used as a reliable source for food records.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have suggested that users were more compliant with dietary tracking using Smartphone apps compared to the traditional paper-and-pencil food diaries [ 13 ], although these findings were inconsistent [ 14 ]. Furthermore, a recent international survey completed by healthcare professionals (including dietitians, doctors and nurses) revealed that 45.5% recommended nutrition apps to their patients [ 15 ].…”
Section: The Advent Of Smartphone Apps In Dietary Surveillancementioning
confidence: 99%